Proveniência dos minerais pesados na planície costeira do Rio Grande do Sul - Carassai, Julierme Justin (Universidade do Vale do Rio dos Sinos, 2017)
Quaternary sandy barriers store the evolutionary history of the last 400,000 years of sedimentation along the southern Brazil Atlantic coast. Studies of provenance allowed to identify the heavy minerals composition of the four barriers in the northern half of the Coastal Plain of the Rio Grande do Sul State: epidote, tourmaline, zircon, magnetite/ilmenite, Alpolymorphs (andalusite, kyanite and sillimanite), staurolite, rutile, amphibole, pyroxene, corundum, perovskite, chromite, garnet, apatite, monazite, xenotime, spinel and titanite. This research contemplated the analysis of the different distribution patterns of minerals in the aeolian and upper shoreface-foreshore systems of each barrier, as well as the behavior of these according to the various particle sizes (80-170 and 170-230 mesh). Studies of provenance developed with a large number of detrital zircon grains by U-Pb allowed to establish the primary source areas for the successive barrier systems. Zircon and other heavy minerals were mainly attributed mainly to a distant source, related to the drainage basin of the Rio de La Plata estuary, and secondary one, associated with the drainage basins of the to the Camaquã and Jacuí rivers. The characterization of the sands origin of the quaternary coastal barriers allowed also the formulation of a hypothesis about the origin of sediments accumulated in the Rio Grande Fan.
Keywords: Barreiras arenosas; Minerais pesados; Planície costeira; Zircão; Sandy barriers; Heavy minerals; Coastal plain; Zircon; ACCNPQ::Ciências Exatas e da Terra::Geologia